The Evolution of Paleolithic Hunting Weapons: A Response to Declining Prey Size - Miki Ben-Dor; Ran Barkai (Quaternary, 2023)
This paper examines the hypothesis that changes in hunting weapons during the Paleolithic were a direct response to a progressive decline in prey size. The study builds upon a unified hypothesis that explains Paleolithic human evolutionary and behavioral/cultural phenomena, including improved cognitive capabilities, as adaptations to mitigate declined energetic returns due to a decline in prey size. Five selected case studies in Africa and Europe were analyzed to test this hypothesis, focusing on the relative presence of megaherbivores (>1000 kg) in the transition between the Acheulean/Early Stone Age and the Middle Paleolithic/Middle Stone Age. The findings indicate a decline in megaherbivores’ presence and biomass contribution in the studied transition period associated with the introduction of Levallois technology. We review the evolution of hunting weapons, including wooden-tipped and stone-tipped spears and bows and arrows. Analysis of tip size and breakage patterns indicate a reduction in point size over time, aligning with the declining prey size. We propose that changes in hunting weapons and strategies were driven by the practical and ontological incentives presented by the availability and size of prey. Developing smaller, more precise weapons required increased cognitive capacities, leading to the parallel evolution of human cognitive abilities.